Percutaneous Cannulation of Femoral Vessels in Minimally Invasive Cardiac Surgery - Sugimura, Yukiharu; Jandali, Hassan; Immohr, Moritz Benjamin; Katahira, Shintaro; Minol, Jan-Philipp; Lichtenberg, Artur; Akhyari, Payam (The Thoracic and Cardiovascular Surgeon, 2022)
Objective Despite the recent trend of access miniaturization in minimally invasive cardiac surgery (MICS) surgical “cut down (CD)” for femoral cannulation remains the standard at many centers. Percutaneous vascular closure (PVC) devices have recently been introduced for minimizing invasiveness during interventional diagnostic and therapy. This report summarizes the initial experience with this new approach in the setting of MICS, with a special focus on safety and advantages.Methods Percutaneous cannulation with a standard protocol including preoperative computer tomography imaging and intraoperative point-of-care ultrasound guidance was performed in 93 consecutive patients from September 2018 until February 2020, while conventional “CD” procedure performed in 218 patients in the previous period. We analyzed patients' characteristics and compared access site complications of PVC group versus conventional “CD” group.Results As far as operative/postoperative outcome, the duration of intensive care unit stay as well as hospital stay was statistically shorter in PVC compared with CD (CD vs. PVC: 2.74 ± 3.83 vs. 2.16 ± 2.01 days, p < 0.01, 16.7 ± 8.75 vs. 13.0 ± 4.96 days, p < 0.001, respectively). Further, we found no femoral infection or lymphocele in the PVC group, whereas 4 cases of wound complications were observed in the CD group.Conclusion According to our results, percutaneous closure system for femoral vessels in MICS seems to be beneficial with the assist of preoperative computed tomography and intraoperative Doppler guidance.
Keywords: minimally invasive cardiac surgery; mitral valve surgery; femoral cannulation; percutaneous vascular closure; ProGlide